INVESTIGATION OF THE INFLUENCE OF PERSONALITY TRAITS IN THE USE OF DIFFERENT MULTIMEDIA ELEMENTS - Reis, Helena Macedo; Kautzmann, Tiago Roberto; Tiosso, Fernando; Borges, ‪Simone de Sousa; Souza, Rodrigo Clemente Thom de; Jaques, Patrícia Augustin (Revista Interface Tecnológica, 2020)
In educational computer systems, media elements have been used as important cognitive tools, capable of supporting the understanding of more complex information. However, when elaborated inappropriately, the media elements can make it difficult to understand the instructions, resulting in a high cognitive effort by the students. To minimize this problem, studies adopt principles and / or guidelines that support the study of more effective multimedia elements during learning, in which information processing is used. However, these studies do not consider individual aspects, such as personality traits. Some studies indicate that personality traits can influence information processing, such as the ability to process visual and auditory information at the same time. This article presents the planning, execution and results of an experiment carried out to investigate how personality traits can affect students' learning, cognitive effort and feelings of frustration when using different multimedia elements. It was observed that some students showed a high degree of anxiety and impatience in using the example worked.
Keywords: Personality traits; Multimedia elements; Cognitive load